2017
DOI: 10.1177/0269215517730670
|View full text |Cite
|
Sign up to set email alerts
|

The impact of self-perceived limitations, stigma and sense of coherence on quality of life in multiple sclerosis patients: results of a cross-sectional study

Abstract: Objective:To examine the impact of perceived limitations, stigma and sense of coherence on quality of life in multiple sclerosis patients.Design:Cross-sectional survey.Setting:Department of Neurology, University Medical Center Groningen, the Netherlands.Subjects:Multiple sclerosis patients.Main measures:World Health Organization Quality of Life – abbreviated version, Stigma Scale for Chronic Illness, Sense of Coherence Scale, background and disease-related questions.Results:In total, 185 patients (61% response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 32 publications
4
29
1
2
Order By: Relevance
“…However, other studies have reported nonsignificant bivariate associations between MS duration and stigma. 3,4 Given the complex association between…”
Section: Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…However, other studies have reported nonsignificant bivariate associations between MS duration and stigma. 3,4 Given the complex association between…”
Section: Surveymentioning
confidence: 99%
“…Over time, MS symptoms tend to progress and can lead to severe disability. 2 Most people with MS experience social stigma as a result of their MS at mild-to-moderate levels, 3,4 with potential implications for their health. Stigma occurs when people are labeled as different, separate, and of lower status based on some characteristic (such as MS), and are thus negatively stereotyped and/or discriminated against.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stigma is a psychosocial challenge that negatively affects the physical and mental health of people living with MS. [5][6][7]21 In recent decades, there has been a major shift in the physician-patient relationship; patients are insisting on playing a more active role in decisionmaking processes related to their medical care. 22 Identifying stigma using easy-to-implement patient-reported instruments might be relevant in terms of greater patient engagement.…”
Section: Discussionmentioning
confidence: 99%
“…6 Individuals with more self-stigma also experienced poorer quality of life in a Dutch study using the World Health Organization quality-of-life measurement instrumentabbreviated version. 7 Perception of stigma was also associated with greater caregiver burden (odds ratio, 3.83; 95% CI, 1.84-7.96) in a survey of 530 patients with MS from Canada. 8 Understanding stigma in MS may be crucial for performing specific intervention strategies against the internalized cognitive, emotional, and behavioral impact of the negative attitudes of others on a patient with a chronic illness.…”
Section: Statistical Analysesmentioning
confidence: 97%